Imaging of Ischemic Stroke. Issue 5 (October 2016) - Lin, Michelle P.; Liebeskind, David S.
Abstract : ABSTRACT: Purpose of Review: This article provides an overview of cerebrovascular hemodynamics, acute stroke pathophysiology, and collateral circulation, which are pivotal in the modern imaging of ischemic stroke that guides the care of the patient with stroke. Recent Findings: Neuroimaging provides extensive information on the brain and vascular health. Multimodal CT and MRI delineate the hemodynamics of ischemic stroke that may be used to guide treatment decisions and prognosticate regarding expected outcomes. Mismatch imaging with either CT or MRI may identify patients with salvageable regions who are at risk and likely to benefit from reperfusion therapy, even if they are outside the standard time window. Imaging of collateral circulation and determination of collateral grade may predict greater reperfusion, lower hemorrhage risk, and better functional outcome. Current neuroimaging technology also enables the identification of patients at high risk of hemorrhagic transformation or those who may be harmed by treatment or unlikely to benefit from it. Summary: This article reviews the use and impact of imaging for the patient with ischemic stroke, emphasizing how imaging builds upon clinical evaluation to establish diagnosis or etiology, reveal key pathophysiology, and guide therapeutic decisions.